Effects of Using Sasobit and SBS on the Engineering Properties of Bitumen and Stone Mastic Asphalt - Kok, Baha Vural; Akpolat, Mustafa (Asce-Amer Soc Civil Engineers, 2015)
Using hard and polymer-modified binders in stone mastic asphalt mixtures reduces workability considerably. In this study, Sasobit (Sasolwax, Worthdamm, Hamburg) is used in bitumen to increase the workability and efficiency of styrene-butadiene-styrene (SBS)-modified binders. The properties of SBS-modified and Sasobit-modified binders and mixtures were evaluated for their rheological and mechanical performances using different experimental techniques such as rheological bitumen tests-i.e., dynamic shear rheometer (DSR), bending beam rheometer (BBR), and hot-mixture performance tests; i.e., dynamic creep, fatigue, and toughness index tests. Sasobit improves the effectiveness of SBS modification, especially at medium to high temperatures, although it is not as flexible as SBS at low temperatures. In some cases, SBS modification is more effective than Sasobit modification when used alone. However, a better performance is achieved when 3% SBS plus 3% Sasobit is used when the two modifiers are mixed in the same binder, especially in terms of fatigue performance. (C) 2015 American Society of Civil Engineers.
Keywords: Styrene-butadiene-styrene (SBS); Sasobit; Rheological properties; Creep; Fatigue